Localization of chitin synthetase in cell-free homogenates of Saccharomyces cerevisiae: chitosomes and plasma membrane. - Leal-Morales, C A (1988)
We describe an improved method for fractionating cell-free extracts of Saccharomyces cerevisiae to separate its membranous components by a combination of isopycnic and velocity sedimentations. These procedures were used to examine the subcellular distribution of chitin synthetase (chitin-UDP acetylglucosaminyltransferase; EC 2.4.1.16) in homogenates from exponentially growing walled cells of a wild-type strain of yeast. Chitin synthetase (Chs1) activity was mainly found in two distinct vesicle populations of nearly equal abundance but with markedly different buoyant densities and particle diameters. One population contained 45-65% of the total chitin synthetase and was identified as chitosomes because of microvesicular size (median diameter = 61 nm) and characteristic low buoyant density (1.15 g/ml); it also lacked 1,3-beta-glucan synthetase activity. The second population (35-55%) was identified as plasma membrane because of its high buoyant density (1.22 g/ml), large vesicle size (median diameter = 252 nm), and presence of vanadate-sensitive ATPase. This fraction cosedimented with the main peak of 1,3-beta-glucan synthetase. A third, minor population of chitin synthetase particles was also detected. Essentially all of the chitin synthetase in the two vesicle populations was zymogenic; therefore, we regard these vesicles as precursors of the final active form of chitin synthetase whose location in the cell has yet to be unequivocally determined.